Gender differences in Anxious-depressive symptomatology, Metabolic Syndrome and Colorectal Adenomas among outpatients undergoing colonoscopy: a cross-sectional study according to a PNEI perspective - Rioli, Giulia; Mattei, Giorgio; Bonamici, Caterina; Mancini, Stefano; Alboni, Silvia; Cannazza, Giuseppe; Sena, Paola; Roncucci, Luca; Pingani, Luca; Ferrari, Silvia; Galeazzi, Gian Maria (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: To explore gender differences in patients suffering from anxious-depressive symptoms, Metabolic Syndrome (MetS) and Colorectal Adenomas (CRAs) in a sample of outpatients undergoing colonoscopy for screening purposes.Methods: Cross-sectional study. 126 consecutive outpatients of both sexes undergoing colonoscopy for non-specific abdominal symptoms between January 2015 and June 2021 at the Modena Policlinico General Hospital (Modena, Northern Italy) were enrolled. MetS was diagnosed according to ATPIII and IDF criteria. Anxiety and depression were assessed with the Hospital Anxiety and Depression Scale (HADS), while the Temperament and Character Inventory (TCI) was used to study personality. The SF-36 was also included as a measure of quality of life perception.Results: Among 126 outpatients (51.60% male) undergoing colonoscopy, 51 (44%) had CRAs, 54 (47%) MetS, 41 (41.40%) anxiety symptoms, 22 (22.20%) depressive symptoms and 13 (13.10%) combined anxious-depressive symptoms. HADS-Anxiety (t=2.68, p=0.01) and TCI Reward Dependence (TCI-RD) (t=3.01, p=0.00) mean scores were significantly higher in women; conversely, SF-36 Mental Component Summary scores were higher in men. CRAs were significantly prevalent in men (χ2=9.32, p=0.00) and were statistically significantly associated with male sex at the univariate logistic regression analysis (OR=3.27; p